PEMBELAJARAN KONTEKSTUAL MELALUI PERMAINAN KELERENG PADA SISWA KELAS III SD UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN - Maria Fatima Mei; Stefania Baptis Seto; Maria Trisna Sero Wondo (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
The purpose of this study was to describe an increase in the ability to understand mathematical concepts, teaching skills of teachers in managing mathematics learning and student learning activities using contextual learning models through marble games. This type of research is Classroom Action Research (PTK). The subjects of the research were 15-grade students of SDI Tetandara. The data collection techniques used were observation, interview, test, and documentation. The instrument in this study used test questions, observation sheets, and interview sheets. Data analysis in this research is quantitative and qualitative data analysis. The results of this study indicate that (1) the increase in teacher activity from pre-cycle to cycle I am 15.75%, cycle I to cycle II is 17.45%. (2) Student activity has increased from the pre-cycle to cycle I by 27%, and cycle I to cycle II by 26%. (3) Increased understanding of the multiplication concept of students in the pre-cycle to cycle I amounted to 26.66% for indicator 1, 20% for indicator 2, 6.67% for indicator 3, and 33.34% for indicator 4. As for the first cycle to cycle II has increased by 26.67% for indicator 1, 26.66% for indicator 2, 33.33% for indicator 3, and 26.66% for indicator 4.